2012
DOI: 10.1074/jbc.m112.351056
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosidase Aggregation Is a Determinant of Pharmacological Chaperone Efficacy on Fabry Disease Mutants

Abstract: Background: Deficiency in ␣-galactosidase activity leads to Fabry disease, for which treatment employing pharmacological chaperones is being developed. Results: Aggregating ␣-galactosidase mutants are not responsive to the treatment with the pharmacological chaperone, 1-deoxygalactonojirimycin (DGJ). Conclusion: Aggregation of ␣-galactosidase is a decisive factor for DGJ efficiency. Significance: Combining pharmacological chaperones treatment with suppression of aggregation might be beneficial for future thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The whole cell extract was separated by centrifugation (29,200 g, 10 min, 4°C) to obtain the soluble fraction. Pellets were then resuspended in an equal volume of denaturing gel loading buffer to obtain the insoluble fraction.…”
Section: Cell Lysis and Western-blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole cell extract was separated by centrifugation (29,200 g, 10 min, 4°C) to obtain the soluble fraction. Pellets were then resuspended in an equal volume of denaturing gel loading buffer to obtain the insoluble fraction.…”
Section: Cell Lysis and Western-blot Analysesmentioning
confidence: 99%
“…SEC analyses of lysates of CHO-GO cells were performed according to the method of Siekierska A. et al [29]. Four 10 cm diameter dishes of confluent CHO-GO-G47R-Mi cells were grown in the absence or in the presence of PN (3 μM), harvested and lysed in 500 μl of PBS as previously described.…”
Section: Size Exclusion Chromatography (Sec)mentioning
confidence: 99%
“…Upon selection, the site affected by the mutation is shown on a space-filling model and colored in yellow or in blue, if it occurs at disulphide bridge sites or in the active site, in magenta otherwise. Recently, it was proposed that mutations promoting protein aggregation do not respond to PC [7]. We ran the program TANGO [8] and we found that a small minority, twelve out of 130 mutations experimentally tested Fabry, is predicted to promote aggregation.…”
Section: Letter To the Editormentioning
confidence: 99%
“…High-throughput DSF screens are used to identify candidate binders to proteins of interest independent of enzymatic activity 7,12,21 . DSF has also been used to search for small-molecule correctors for genetically destabilized proteins [22][23][24][25] which underlie many misfolding diseases 13,26,27 such as cystic fibrosis 28,29 , Gaucher's disease 30 and Fabry's disease 31 . For example, our lab conducted a primary chemical screen by DSF to identify ligands for cataract-associated forms of alpha B-crystallin 32 .…”
Section: Introductionmentioning
confidence: 99%